Starting Early: Understanding Higher Education Admission in Europe - Atherton, Graeme (International Higher Education, 2025)
As demographic changes coincide with a desire to widen access to higher education, higher education admission systems in Europe take on increasing significance. Given that admission criteria often effectively begin many years prior to the completion of compulsory education, however, reform will require engagement from more than one level of the school system.